165k views
0 votes
Which formula can be used to find the nth term of the following geometric sequence? − 2/9 , 2/3 , −2, 6,…

User Niklasbec
by
5.6k points

2 Answers

1 vote

Final answer:

The formula to find the nth term of a geometric sequence is an = a1 * r(n-1). In the given sequence, the formula would be an = (-2/9) * (2/3)(n-1).

Step-by-step explanation:

The formula to find the nth term of a geometric sequence is:



an = a1 * r(n-1)



Where:



  • an is the nth term
  • a1 is the first term
  • r is the common ratio
  • n is the number of terms



In the given sequence, the first term (a1) is -2/9 and the common ratio (r) is 2/3. Therefore, the formula to find the nth term is:



an = (-2/9) * (2/3)(n-1)

User Rdllopes
by
5.7k points
1 vote

Answer:


a_n=-(2)/(9)(-3)^(n-1)

Step-by-step explanation:

Since, the nth term of a geometric sequence is,


a_n=ar^(n-1)

Where, a is the first term of the sequence,

r is the common ratio,

Here, the given geometric sequence is,


-(2)/(9),(2)/(3),-2,6........

Thus, the first term of the sequence is,


a=-(2)/(9)

And, the common ratio,


r=(2/3)/(-2/9)=-3

Hence, the nth term of the sequence is,


a_n=-(2)/(9)(-3)^(n-1)

User Omer Bach
by
6.0k points